Hey folks,(adsbygoogle = window.adsbygoogle || []).push({});

I'm trying to show that [tex]\sum_{m,n=-\infty}^\infty '(n^2+a^2m^2)^{-s}=\sum_{n=-\infty}^\infty 'n^{-2s}+\sum_{m=-\infty}^\infty'\sum_{n=-\infty}^\infty(n^2+a^2m^2)^{-s}[/tex]. The prime means that we don't include the m=n=0 term.

Has anyone seen this relation? Is it standard?

Thanks!

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Decomposition of Double Sum

**Physics Forums | Science Articles, Homework Help, Discussion**